Early transcriptomic changes at the skin interface during Powassan virus transmission by Ixodes scapularis ticks - Dakota N. Paine; Dakota N. Paine; Meghan Hermance; Saravanan Thangamani; Saravanan Thangamani; Saravanan Thangamani (Frontiers in Immunology)
IntroductionPowassan virus (POWV), a vector-borne pathogen transmitted by Ixodes ticks in North America, is the causative agent of Powassan encephalitis. As obligate hematophagous organisms, ticks transmit pathogens like POWV at the tick bite site, specifically during the initial stages of feeding. Tick feeding and salivary factors modulate the host’s immunological responses, facilitating blood feeding and pathogen transmission. However, the mechanisms of immunomodulation during POWV transmission remain inadequately understood. In this study, we investigated the global cutaneous transcriptomic changes associated with tick bites during POWV transmission.MethodsWe collected skin biopsies from the tick attachment sites at 1, 3, and 6 h after feeding by POWV-infected and uninfected ticks, followed by RNA sequencing of these samples. Differentially expressed genes were analyzed for pathway enrichment using gene ontology and pathway enrichment analyses.ResultsOur findings reveal that tick feeding alone significantly impacts the skin transcriptome within the first 1 to 3 h of tick attachment. Although early POWV transmission induces minimal changes in the local environment, a pronounced shift toward a proinflammatory state is observed 6 h after tick attachment, characterized by neutrophil recruitment and interleukin signaling.DiscussionThese transcriptomic data elucidate the dynamic changes at the tick bite site, transitioning from changes that assist blood meal acquisition to a proinflammatory phase that may facilitate viral dissemination.